Role of fibreoptic bronchoscopy and CT guided FNAC in diagnostic evaluation of Non resolving Pneumonia with special emphasis on clinical outcome - Jain, Bhupendra Kumar; Sharma, Pooja; Bajpai, Ashok; Motiwale, Satish; Pasari, Nikhilesh; Patel, Deepika (Asian Journal of Medical Sciences, 2014)
Background: Nonresolving pneumonia is a pneumonia with a delayed or slow resolution of radiographic infiltrates or clinical symptoms despite adequate treatment with antibiotics for a minimum period of 10 days. Fibreoptic bronchoscopy (FOB) and CT guided FNAC has a specific role in diagnosis of Non resolving pneumonia. Aims and Objectives: To assess the diagnostic efficacy of fibreoptic bronchoscopy (FOB) and computed tomography (CT)- guided fi ne needle aspiration cytology (FNAC) in evaluation of non-resolving or slowly resolving pneumonia with special emphasis on clinical outcome. Material and Methods: The study was designed as a prospective observational study. We reviewed FOB in Sixty-five consecutive patients of Non-resolving pneumonia admitted under Respiratory Medicine unit of Sri aurobindo medical college and PG Institute Indore from June 2012 to May 2014. We also reviewed role of CT guided FNAC in selected case where FOB result was inconclusive. Result: Out of total Sixty-five case of non resolving pneumonia, Fifty-two patient (81%) were diagnosed with the help of FOB and Eleven patients (91%) were diagnosed with help of CT guided FNAC out of Twelve patient subjected for procedure. Conclusion: FOB should be the first option before CT-guided FNAC in evaluating non-resolving pneumonia. Both the procedures were safe and no major complication was observed. DOI: http://dx.doi.org/10.3126/ajms.v6i3.10727 Asian Journal of Medical Sciences Vol.6(3) 2015 66-71